The Hadith Interpretations of Radical-Terrorist Groups - Arromadloni, Muhammad Najih; Al Munawar, Said Agil Husin; Mansurnoor, Iik Arifin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2022)
Radical groups were known to deconstruct the meaning of hadith, especially those related to the themes of the caliphate, jihad, hijrah, faith, and the end of time. They put aside the context of the background of the hadith so that it only clumped up as a text without having a fundamental historical basis. The pattern of understanding applied was also contrary to the principal rules of hadith studies which were well-known among scholars and hadith reviewers. The four radical groups examined in this study were the Ikhwanul Muslimin (IM), Hizb al-Tahrir (HT), Al-Qaeda, and the Islamic State of Iraq and Syria (ISIS). Despite having different characteristics of thought and movement, the four radical-terrorist groups had similarities in terms of exploiting the meaning and function of hadith to legitimize their acts of terror. The findings in this study confirmed the views of scholars who argued that understanding of hadith could be reduced by the interests and problems of power politics that were increasingly complex from time to time.